Covid-19 and Acute Kidney Injury: Recent Updates - Shafi, Salman Tahir (Pakistan Journal of Kidney Diseases, 2021)
In January 2020, the pathogen was identified and named by the World Health Organization as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2). The consequent SARS-CoV-2-related disease was defined as coronavirus disease 2019 (COVID-19). As data emerged about characteristics of the disease, it was found to be associated with increased risk of acute kidney injury (AKI). We explore the recent literature and reports emerging from the epicenters of the pandemic to help our viewers understand the nature of AKI among these patients.